Pemanfaatan Limbah Cangkang Telur dan Maggot sebagai Bahan Baku Alternatif dalam Formulasi Pakan Pelet Kaya Kalsium dan Protein - Auliana Nurutsani Umaya; Levina Mutiara Alfarel; Mutiara Ni’matul Maula; Bambang Suwerda (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Organic waste management at Yogyakarta International Airport (YIA) is still not optimal, even though organic waste production averages 1,264 kg per month. This community service activity aims to develop technological innovations through the utilization of eggshell waste and Black Soldier Fly (BSF) maggots into economically valuable pellet feed products. The activity was carried out from October 8 to 15, 2025, involving three workers from the Temporary Processing Site (TPS) of PT Angkasa Pura Indonesia YIA. The implementation methods included an initial survey, education, demonstration of pellet production, and evaluation of participants' skills and product quality. The production process involved drying, grinding the ingredients, mixing the ingredients, molding, and drying the pellets. The results showed that the workers were able to independently carry out the production process and produce pellets with good physical quality. Cost analysis showed that the cost of production was IDR 47,989/kg, with a potential profit margin of 30% and an estimated return on investment within ±7 months. This innovation has proven effective in reducing waste volume, increasing the added value of organic waste, and supporting the principles of zero waste and circular economy in the airport area. This program has the potential to be further developed as a model for sustainable organic waste management.